Digital resources and didactic methodology in the initial training of History teachers - Miralles-Martínez, Pedro; Gómez-Carrasco, Cosme J; Arias, Víctor B; Fontal-Merillas, Olaia (Comunicar, 2019)
This paper analyzes the links that exist between the perceptions of teachers-in-training regarding the use of digital resources in the Secondary Education classroom and their own methodological and epistemological conceptions. Shulman's theories continue to largely guide current research on teacher knowledge. However, the impact caused by the new technologies has inspired new approaches like T-PACK, which put the focus on the teachers' digital competence. In order to address this goal, information has been collected by means of a questionnaire implemented in 22 universities, 13 Spanish (344 participants) and 9 British (162 participants). The analysis of data was conducted along three phases: a) examination of the structure of assessments regarding the usefulness of digital resources by analyzing latent classes; b) estimation of confirmatory factor models for variable evaluation processes, History as a formative subject and historical competencies; c) estimation of interclass differences by using confirmatory factor models. The results showed four types of response regarding the use of digital resources in the classroom that were polarized about two items: comics and video games. Important interclass differences have likewise been found regarding methodological issues (traditional and innovative practices), as well as less important differences concerning epistemological conceptions and views on the development of historical competencies in the classroom.